ДІАЛЕКТИКА НАЦІОНАЛЬНОГО І ТРАНСНАЦІОНАЛЬНОГО В СУЧАСНОМУ СВІТІ - Цимбал, Т. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
У статті пропонується досвід осмислення проблеми національної ідентичності в добу глобалізації. Автором сформульовано головну задачу сучасних суспільних наук, а саме: деполітизація етнонаціональних відносин. Розглянуті вихідні принципи та способи формування транснаціональної ідентичності як основи соціальної гармонії. Цимбал Т.В. Диалектика национального и транснационального в современном мире. В статье предлагается опыт осмысления проблемы национальной идентичности в эпоху глобализации. Автором сформулирована главная задача современных общественных наук, а именно: деполитизация этнонациональных отношений. Рассмотрены исходные принципы и способы формирования транснациональной идентичности как основы социальной гармонии. Tatyana Tsymbal. Dialectics of national and transnational in the modern world. In this article the experience of comprehension of the problem of national identity in the era of globalization is considered. The author formulated the main task of the modern social sciences: depoliticization of the ethno national relations. Initial principles and ways of forming of transnational identity as the basis of social harmony are considered.